The diagnostic value of passive leg raise during right heart catheterization in diagnosing heart failure with preserved ejection fraction. (25th November 2020) - Van De Bovenkamp, A.A; Wijkstra, N; Braams, N.J; Jansen, M.A; Oosterveer, F.P.T; Bogaard, H.J; Van Rossum, A.C; De Man, F.S; Handoko, M.L
Abstract: Background: Heart failure with preserved ejection fraction (HFpEF) is a frequent and disabling disease, but can be difficult to diagnose. Due to limited sensitivity of non-invasive evaluation of left ventricular (LV) diastolic dysfunction, invasive measurement may be warranted. The gold standard for diagnosing HFpEF is invasive measurement of LV end-diastolic pressure or its surrogate pulmonary capillary wedge pressure (PCWP). In case of normal LV filling pressures at rest (PCWP@rest <16 mmHg), patients should undergo stress testing to unmask occult HFpEF (early HFpEF if PCWP@exercise ≥25mmHg). Performing exercise during a right heart catheterization is time-consuming and logistically challenging. Passive leg raise increases venous return and can lead to an abnormal increase in LV filling pressures in case of diastolic dysfunction. Whether this leg raise maneuver (PCWP@legraise) can be used as an accurate method to diagnose or exclude HFpEF and what cut-off values should be used is unknown. Purpose: To assess the diagnostic value of PCWP@legraise during right heart catheterization for HFpEF. Methods: We reviewed all consecutive patients who received a diagnostic right heart catheterization with PCWP-measurements at rest, passive leg raise and during exercise (minimally >40% peak VO2) between 2017 and 2020 in a tertiary medical center (n=124). Zero reference point was defined mid-thorax. PCWP was measured end-expiratory mid A-wave. Patients with insufficient data (n=17), uninterpretable tracings (n=13) or PCWP@rest >16 mmHg were excluded (n=19). The diagnostic value of PCWP@legraise was compared to the gold standard for HFpEF (PCWP@exercise). Results: We analyzed 75 patients, with a mean age of 58 (±16) years, female (60%), mean BMI 27.8 (±5.5). HFpEF was diagnosed in 47% of the cases, non-HFpEF existed of pulmonary arterial hypertension (23%), chronic thrombo-embolic disease (15%) or other (15%). Figure 1A shows PCWP@rest, PCWP@legraise, PCWP@exercise for HFpEF and non-HFpEF. The diagnostic performance of PCWP@legraise was higher than PCWP@rest (Figure 1B; AUC 0.83 vs 0.75). PCWP@legraise ≥22 mmHg had a specificity of 100% and a positive predictive value of 100% for diagnosing HFpEF and could be used as a cut-off for diagnosing HFpEF. PCWP@legraise of ≥13 mmHg had a sensitivity of 98% and a negative predictive value of 93%, and could be used as a cut-off for excluding HFpEF. If these cut-offs were used to refute or diagnose HFpEF, 17 patients (23%) could have been differed from exercise during right heart catheterization. The change in PCWP due to passive leg raise was of lower diagnostic value than the absolute value of PCWP@legraise. Conclusion: In our cohort, the leg raise maneuver is of diagnostic value. With the proposed PCWP@legraise criteria for HFpEF - validated against the gold standard (PCWP@exercise) - the exercise could have been omitted in almost a quarter of the cases. More (external) validation is warranted. Funding Acknowledgement: Type of funding source: None